The Concept of Peace in the Al-Qur'an Pespective - Mukhtar Nuhung; Abdul Rahim (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
Conflicts, disputes, and acts of terrorism have become a daily scene, both in the nature of individuals, communities, tribes, religions, and even between nations. Al-Quran as a way of live always leads Muslims to live safely and peace away from the conflict. Thus, the main problem arising from this research is how the concept of peace in the Qur'an. This discussion aims to know how the nature of peace, how the form of peace, and how the goals and benefits of peace according to the Qur'an. It is intended to provide a comprehensive understanding of the concept of peace that exists in the Quran. The research is a library research which is qualitative. Data and information obtained through several literatures were analyzed using content analysis. The approach used was the